PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PT. AGRO MUKO BUNGA TANJUNG ESTATE - Selvi Yona Tamara; Tri Andi Eka Putra; Fhajri Arye Gemilang (Nusantara Hasana Journal, 2022)
This study aims to determine how much influence Organizational Culture, Work Environment together (simultaneously) and partially on Employee Performance with Work Motivation as an Intervening Variable. Methods of collecting data through surveys and questionnaires. The analytical method used is the validity and reliability test, correlation analysis, multiple linear analysis, to test the hypothesis used t test The sample of this company amounted to 79 respondents.